2020
DOI: 10.3324/haematol.2019.245688
|View full text |Cite
|
Sign up to set email alerts
|

History of hematopoietic cell transplantation: challenges and progress

Abstract: After more than 60 years of research in allogeneic hematopoietic cell transplantation (HCT), this therapy has advanced from one that was declared dead in the 1960s to a standard treatment of otherwise fatal malignant and non-malignant blood diseases. To date, close to 1.5 million hematopoietic cell transplants have been performed in more than 1,500 transplantation centers worldwide. This review will highlight the enormous efforts by numerous investigators throughout the world who have brought the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 175 publications
(160 reference statements)
0
50
0
5
Order By: Relevance
“…Hematopoietic cell transplantation (HCT) is a potentially curative treatment for high-risk hematopoietic neoplastic disorders, metabolic, genetic and immune-mediated diseases. It involves eradication or suppression of the recipient's hematopoietic cells using a conditioning regimen followed by infusion of stem cells collected from the bone marrow, placenta (cord blood) or peripheral blood (1). The source of hematopoietic cells can be either autologous (auto, recipientderived) or allogeneic (allo, matched related or unrelated donor-derived) hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic cell transplantation (HCT) is a potentially curative treatment for high-risk hematopoietic neoplastic disorders, metabolic, genetic and immune-mediated diseases. It involves eradication or suppression of the recipient's hematopoietic cells using a conditioning regimen followed by infusion of stem cells collected from the bone marrow, placenta (cord blood) or peripheral blood (1). The source of hematopoietic cells can be either autologous (auto, recipientderived) or allogeneic (allo, matched related or unrelated donor-derived) hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…A study in the USA found significantly greater 1-year post-alloHSCT costs for patients with aGvHD compared to those without aGvHD ($466,720 vs. $263,568; P < 0.001), with inpatient care being the primary cost driver [43]. A Swedish real-world study found that the cumulative direct medical costs over 3 years post-alloHSCT for patients Table 1 Summary of graft-versus-host disease (GvHD) in allogeneic haematopoietic stem cell transplantation (alloHSCT) Note: AlloHSCT outcomes are dependent on multiple factors, making it difficult to provide generally applicable ranges, especially when considering recent trends of improved alloHSCT procedures and regimens [31,36]. Relevant factors include recipient age, patient fitness/co-morbidities, underlying malignant/non-malignant disease, graft source, donor type/age, conditioning regimen, pre alloHSCT treatment, GvHD prophylaxis and post-alloHSCT treatment a Transplant-related mortality defined as death unrelated to relapse or disease progression…”
Section: Key Pointsmentioning
confidence: 99%
“… Note: AlloHSCT outcomes are dependent on multiple factors, making it difficult to provide generally applicable ranges, especially when considering recent trends of improved alloHSCT procedures and regimens [ 31 , 36 ]. Relevant factors include recipient age, patient fitness/co-morbidities, underlying malignant/non-malignant disease, graft source, donor type/age, conditioning regimen, pre alloHSCT treatment, GvHD prophylaxis and post-alloHSCT treatment a Transplant-related mortality defined as death unrelated to relapse or disease progression …”
Section: Graft-versus-host Disease (Gvhd) Is a Life-threatening And Expensive Complication Of Allogeneic Haematopoietic Stem Cell Transplmentioning
confidence: 99%
“…The use of h-BMSCs as a therapy to modulate immune responses is known. In fact, it has been shown that these cells can express histamine H1, H2, and H4 receptors and histamine itself then stimulating the production of interleukin 6 (IL-6) [ 18 20 ]. Finally, several studies mention the role of stem cells in the relationship with periodontitis antibodies and particularly in CVD (cardiovascular disease) biomarkers in the early stages.…”
Section: Introductionmentioning
confidence: 99%
“…To date, three stem cell-based therapies have been considered: (a) already differentiated cell transplantation with specific types of cells that derive from embryonic or somatic stem cells and include patient's own stem cells and grow and differentiate under special processing conditions in the laboratory (e.g., insulin-producing cells for the treatment of diabetes), (b) stimulation of endogenous stem cells in an individual (e.g., by administering growth factors) with the possibility of inducing or increasing the processes of selfrepair, and (c) direct administration of stem cells to the patient, so that a colonization process begins in the desired part of the body and thus the differentiation continues into the desired cell type (Figure 2) [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%